Bridging the digital divide: Unlocking growth for grain and agro-processing businesses in Tanzania - Mwakatwila, Atupokile; Ochieng, Justus; Lesedy, Victor; Radegunda, Kessy; Majambele, Martin (2025)
Digital inclusion is unlocking new opportunities for growth and efficiency in Tanzania’s grain and agro-processing sector, especially for traders and processors working with smallholder farmers. Despite the availability of digital tools, adoption remains low due to limited digital literacy, poor infrastructure, and high upfront costs. The ACCELERATE Project, led by the Alliance of Bioversity International and CIAT, is working to close this gap by connecting traders with digital service providers and building capacity across the value chain. A stakeholder meeting in Dodoma in April 2025 showcased how digital platforms can improve record-keeping, transparency, market access, and farmer engagement in crops such as beans, groundnuts, and sorghum. While traders recognized these benefits, they also highlighted key barriers to adoption. Addressing these challenges requires localized training, tailored solutions, peer learning, and supportive policies to ensure inclusive digital transformation across agricultural markets.